2003
DOI: 10.1002/ardp.200300734
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis andin vitro evaluation of the anticancer activity of novel fluorinated thiazolo[4, 5-d]pyrimidines

Abstract: The synthesis of several thiazolo[4, 5-d]pyrimidines containing a fluorophenyl moiety substituted at different positions and through different bridges is described. Twenty new compounds were prepared and evaluated for their anticancer activity using the USA-NCI in-vitro screening program. Three compounds were found active and their anticancer activity against 60 human tumor cell lines are described in detail.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
17
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…In view of the aforementioned facts, and as a continuation of an on-going research program devoted to the synthesis and characterization of different heterocyclic ring systems endowed with potential chemotherapeutic activities [31][32][33][34][35][36][37][38][39][40][41][42][43], it was sought of interest to design and synthesize certain chalcones and some derived pyrazole, pyrimidine, and thiazolopyrimidine cyclized ring structures substituted basically with polymethoxy groups based on the fact that incorporation of alkoxy substituents would result in significant enhancement of several biological activities due to the magnification of compounds' lipophilicity [44][45][46]. The newly synthesized compounds were designed so as to comprise two polymethoxylated aryl rings attached to either a pyrazole ring substituted with formyl, acetyl or substituted aryl moieties, or a pyrimidine counterpart with different ketone, thione, and thioether functionalities.…”
Section: Introductionmentioning
confidence: 99%
“…In view of the aforementioned facts, and as a continuation of an on-going research program devoted to the synthesis and characterization of different heterocyclic ring systems endowed with potential chemotherapeutic activities [31][32][33][34][35][36][37][38][39][40][41][42][43], it was sought of interest to design and synthesize certain chalcones and some derived pyrazole, pyrimidine, and thiazolopyrimidine cyclized ring structures substituted basically with polymethoxy groups based on the fact that incorporation of alkoxy substituents would result in significant enhancement of several biological activities due to the magnification of compounds' lipophilicity [44][45][46]. The newly synthesized compounds were designed so as to comprise two polymethoxylated aryl rings attached to either a pyrazole ring substituted with formyl, acetyl or substituted aryl moieties, or a pyrimidine counterpart with different ketone, thione, and thioether functionalities.…”
Section: Introductionmentioning
confidence: 99%
“…These designed thiazolo[4,5- d ]pyrimidine-2-ones are related to thiazolo[4,5- d ]pyrimidine-2-thiones that have been previously reported to be potent antitumor agents (Becan and Wagner, 2008). Thiazolo[4,5- d ]pyrimidine derivatives have been extensively studied as potential drug candidates and also have anticancer activity (Rida et al ., 1996; Fahmy et al ., 2002, 2003). Most of these compounds provided with anticancer activity possess an aromatic rings and electronegative substituent directly linked to the C-17 of the essential core (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Careful literature survey revealed that many substituted thiazoles and thiazolo [4,5-d] pyrimidines have been reported to possess anticancer [16][17][18][19][20], antiviral [21][22][23][24][25], and antimicrobial [26][27][28][29] activities. In addition, a family of 2-pyridinone derivatives has been found to be potent and selective non-nucleoside inhibitors of HIV-reverse transcriptase [30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%